Trovatori petrosi. Marcabru, Raimbaut d’Aurenga, Arnaut Daniel: (Carte Romanze, 2023)
This work develops the relationship between Dante’s ‘petrose’ and the ‘clus’ line of trobar and its main representatives. In the development of Dante’s composition technique we can observe moments of returns, retractions and overcoming of models: the mediation of Guittone as a filter for the formation of a canon of ‘uncomfortable troubadours’ is therefore essential to understand Dante’s debt to the previous tradition. The investigation also promotes Raimbaut d’Aurenga as an important troubadour within the line of development that will lead to Arnaut Daniel’s sestina and to Dante.
Keywords: Troubadours; Dante and the troubadours; intertextuality; Dante’s models